An unexpected cause of proximal myopathy. (29th June 2012) - Townsend, Sarah Ann; Smith, Matt; Harris, Wyn; Chudleigh, Richard
Abstract : A 25-year-old man presented with a short history of profound proximal muscle weakness such that he was unable to stand. Laboratory investigations demonstrated hypokalaemia and mildly elevated serum creatine kinase. He reported a history of 8–10 episodes of less severe weakness in the preceding 8 years and his mother reported similar symptoms. The combination of weakness and hypokalaemia with a probable family history suggested the diagnosis of hypokalaemic periodic paralysis. He was treated with intravenous and oral potassium supplementation, and regained full power within 24 h.